2011
DOI: 10.1007/s11010-011-0864-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and nitrite dynamics under maximal load in elite athletes: relation to sport type

Abstract: Maximal workload in elite athletes induces increased generation of reactive oxygen/nitrogen species (RONS) and oxidative stress, but the dynamics of RONS production are not fully explored. The aim of our study was to examine the effects of long-term engagement in sports with different energy requirements (aerobic, anaerobic, and aerobic/anaerobic) on oxidative stress parameters during progressive exercise test. Concentrations of lactates, nitric oxide (NO) measured through stabile end product-nitrites (NO(2) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…The absence of change in the Tae Bo group may be explained by the effect of increased shear stress on endothelium, characteristic for high-intensity aerobic exercise. Numerous previous studies have shown that regular endurance activity increases the bioavailibity of NO (23)(24)(25) and that physically active people have greater basal NO production compared with a sedentary population (26,27). Finally, the observed differences between the groups in the levels of SOD at the beginning of the study may be explained by the more active lifestyle of subjects who chose to be engaged in training, and they likely do not represent the control group.…”
Section: Discussionmentioning
confidence: 92%
“…The absence of change in the Tae Bo group may be explained by the effect of increased shear stress on endothelium, characteristic for high-intensity aerobic exercise. Numerous previous studies have shown that regular endurance activity increases the bioavailibity of NO (23)(24)(25) and that physically active people have greater basal NO production compared with a sedentary population (26,27). Finally, the observed differences between the groups in the levels of SOD at the beginning of the study may be explained by the more active lifestyle of subjects who chose to be engaged in training, and they likely do not represent the control group.…”
Section: Discussionmentioning
confidence: 92%
“…Some studies reported NO increase with exercise, some reported no change in NO production and some reported a decrease in NO production with exercise (Jungersten et al 1997;Poveda et al 1997;St. Croix et al 1999;Allen et al 2006;Allen et al 2009;Rassaf et al 2007;Djordjevic et al 2010a,b;Cubrilo et al 2011;Jakovljevic et al 2011). Those differences are probably due to different protocols, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nitrite concentrations in rest were the lowest in taekwondo fighters, while rowers had the highest levels among examined groups. 9 It is thought that ROS are not produced excessively under physiological conditions in healthy subjects. It has been reported that the massive increase in oxygen uptake that occurs in skeletal muscle during exercise is associated with an increase in the generation of ROS (as superoxide).…”
Section: Discussionmentioning
confidence: 99%
“…For example, nitrite concentrations in rest were the lowest in taekwondo fighters, while rowers had the highest levels among the examined groups. 9 The extent of oxidative stress induced by acute bout of exercise depends on many factors, as well as, exercise mode, intensity and duration, because different modes of exercise differ in energy demands, oxygen consumption and mechanical stress to tissues. 10 Therefore, exercise intensity is clinically also quite important to select the appropriate kind of exercise, because an intense exercise can be hazardous to human vessels.…”
Section: ö öZ Ze Et T Amentioning
confidence: 99%